The politics of names: rethinking the significance of naming a discipline from biblical archaeology to the archaeology of the Near East (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
This paper examines the trends in terminology for the archaeological practice in Israel and Palestine through time. The adoption of terms from 'Biblical Archaeology' to the archaeology of a specific age in a determined geographical area appears to reflect not only the research scope but also its political agenda. After an overview of the most common terminology in the literature, the paper addresses how these names can affect the practice of archaeology in the region of the Near East, in an appeal for its practitioners to the theoretical aspects of the discipline.